FGF20 and PGM2 variants are associated with childhood asthma in family-based whole-genome sequencing studies. Issue 4 (18th October 2022) - Hecker, Julian; Chun, Sung; Samiei, Ahmad; Liu, Cuining; Laurie, Cecelia; Kachroo, Priyadarshini; Lutz, Sharon M; Lee, Sanghun; Smith, Albert V; Lasky-Su, Jessica; Cho, Michael H; Sharma, Sunita; et al.
Abstract: Background: Asthma is a heterogeneous common respiratory disease that remains poorly understood. The established genetic associations fail to explain the high estimated heritability, and the prevalence of asthma differs between populations and geographic regions. Robust association analyses incorporating different genetic ancestries and whole-genome sequencing data may identify novel genetic associations. Methods: We performed family-based genome-wide association analyses of childhood-onset asthma based on whole-genome sequencing (WGS) data for the 'The Genetic Epidemiology of Asthma in Costa Rica' study (GACRS) and the Childhood Asthma Management Program (CAMP). Based on parent–child trios with children diagnosed with asthma, we performed a single variant analysis using an additive and a recessive genetic model and a region-based association analysis of low-frequency and rare variants. Results: Based on 1180 asthmatic trios (894 GACRS trios and 286 CAMP trios, a total of 3540 samples with WGS data), we identified three novel genetic loci associated with childhood-onset asthma: rs4832738 on 4p14 (P=1.72*10^-9, recessive model), rs1581479 on 8p22 (P=1.47*10^-8, additive model) and rs73367537 on 10q26 (P=1.21*10^-8, additive model in GACRS only). Integrative analyses suggested potential novel candidate genes underlying these associations: PGM2 on 4p14 and FGF20 on 8p22. Conclusion: Our family-based whole-genome sequencing analysis identified three novel genetic loci for childhood-onset asthma. Gene expression data and integrative analyses point to PGM2 on 4p14 and FGF20 on 8p22 as linked genes. Furthermore, region-based analyses suggest independent potential low-frequency/rare variant associations on 8p22. Follow-up analyses are needed to understand the functional mechanisms and generalizability of these associations.